EGS++: Optimasi parameter transport dalam simulasi - Sitti Yani (Universitas Andalas, 2023)
MC transport parameters used are common to all egs++ applications. The eﬀect of each transport parameter need to understand to optimize the simulation process. Therefore, the purpose of this study was to investigate the efficiency of egs++ simulation for different transport parameters in water phantom. This water phantom has built using slab. Collimated source defined 100 cm above the phantom. The simulation parameters such as the efficiency, statistical uncertainty, and accuracy of selecting transport parameters such as electron and photon cut-oﬀ energies, spin eﬀects, atomic relaxations, and bound Compton scattering was investigated. The selection of ECUT and PCUT greatly affects the simulation time. The simulation time, efficiency and energy fractions have same value for varied ECUT except for 0.521 MeV. The energy fraction have been shifted but the simulation time and efficiency were same. Turning on spin effects in this simulation increases simulation time by 25%. The simulation time increases by about 15% when relaxations are turned on. The more accurate result of deposited energy using EGSnrc algorithm is about 30% slower than the less accurate PRESTA-I algorithm. Therefore, The optimization of transport parameters is needed in the simulation of egs++ to provide the best efficiency.